A discovery‐driven approach to elucidate urinary metabolome changes after a regular and moderate consumption of beer and nonalcoholic beer in subjects at high cardiovascular risk. Issue 10 (20th July 2017) - Quifer‐Rada, Paola; Chiva‐Blanch, Gemma; Jáuregui, Olga; Estruch, Ramon; Lamuela‐Raventós, Rosa M.
Abstract : Scope: The aim of this work was to study the urinary metabolomics changes of participants that consumed beer, nonalcoholic beer (na‐beer), and gin. Methods and results: Thirty‐three males at high cardiovascular risk between 55 and 75 years old participated in an open, randomized, crossover, controlled trial with three nutritional interventions consisting of beer, na‐beer, and gin for 4 wk. Diet and physical activity was monitored throughout the study and compliance was assessed by measurement of urinary isoxanthohumol. Metabolomic analysis was performed in urine samples by LC coupled to an LTQ‐Orbitrap mass spectrometer combined with univariate and multivariate statistical analysis. Ten metabolites were identified. Eight were exogenous metabolites related to beer, na‐beer, or gin consumption, but two of them were related to endogenic changes: hydroxyadipic acid linked to fatty acid oxidation, and 4‐guanidinobutanoic acid, which correlated with a decrease in urinary creatinine. Plasmatic acylcarnitines were quantified by targeted MS. A regular and moderate consumption of beer and na‐beer decreased stearoylcarnitine concentrations. Conclusion: Humulinone and 2, 3‐dihydroxy‐3‐methylvaleric acid showed to be potential biomarkers of beer and na‐beer consumption. Moreover, the results of this trial provide new evidence that the nonalcoholic fraction of beer may increase fatty oxidation. Abstract : Moderate alcohol consumption has been inversely associated with cardiovascular disease and all‐cause mortality. However, it is thought that fermented alcoholic beverages, such as wine or beer, may provide additional protective effects due to their polyphenolic content. This work aims to evaluate changes in the urinary metabolomic profile due to beer, nonalcoholic beer, and gin (an alcoholic polyphenol free beverage) intake.